2000
DOI: 10.1007/s002280000149
|View full text |Cite
|
Sign up to set email alerts
|

Drug use in pregnancy among Italian women

Abstract: Seventy-five percent of the women reported use of at least one drug during pregnancy. Haematological and nutritional drugs are over prescribed. Although hormones have been clearly proven to be ineffective in preventing threatened abortion, the study shows an almost unchanged and out of date prescription pattern of progestational drugs. In order to avoid unnecessary exposure to potential risk, maternity care procedures should be reviewed and strictly related to an "evidence-based" approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
36
5
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 0 publications
15
36
5
5
Order By: Relevance
“…Data of our study cohort revealed a slightly lower prevalence of medication usage (40 %(95 %CI:35-44 %)) but the trend of increasing consumption is in line with an American study which observed that over the last three decades, use of prescription drugs during pregnancy has increased by over 60 % (49). There are several studies that observed an association between higher maternal education and more prevalent use of medication during pregnancy (49,50,51,52). Contrary to these, others reported more prevalent use of medications among pregnant women with lower education (5,53,54).…”
Section: Discussionsupporting
confidence: 87%
“…Data of our study cohort revealed a slightly lower prevalence of medication usage (40 %(95 %CI:35-44 %)) but the trend of increasing consumption is in line with an American study which observed that over the last three decades, use of prescription drugs during pregnancy has increased by over 60 % (49). There are several studies that observed an association between higher maternal education and more prevalent use of medication during pregnancy (49,50,51,52). Contrary to these, others reported more prevalent use of medications among pregnant women with lower education (5,53,54).…”
Section: Discussionsupporting
confidence: 87%
“…In several studies, anti-infectives were the drugs most prescribed during pregnancy [8,13,19,21]. "Alimentary tract and metabolism" class drugs, which are at the top in our study, were prescribed far less frequently in other countries (80% versus 4 to 10% depending on the study).…”
Section: Discussionmentioning
confidence: 50%
“…The rate of pregnant women having received at least one drug prescription is as high as in many other studies carried out in the United States, Germany or Norway [13,18,19]. In other countries such as Finland, Italy, the Netherlands and the United Kingdom [8,12,[20][21][22], the rate is slightly lower [63, (70, 75), 79 and 65%, respectively). The average number of different active ingredients prescribed per woman is still higher in France compared with the other countries (11.3 versus 1.2 to 7).…”
Section: Discussionmentioning
confidence: 78%
“…Diversos estudos mostram que o consumo de medicamentos está associado a ter problemas de saúde, inclusive durante a gestação 18,45,46 . Mesmo em países desenvolvidos, como o Canadá, por exemplo, um estudo de base populacional encontrou que ter uma doença crônica (OR = 2,01; IC95%: 1,98-2,05) deixou as gestantes mais susceptíveis a receberem prescrições de medicamentos durante a gravidez 46 .…”
Section: Discussionunclassified